Knowledge, Attitude, and Practice (KAP) of mothers regarding Neonatal Jaundice in the hospital of KPK, Pakistan - Sami Ullah Saddozai, Jaweria Gul, Rizwan Shukat, Norina Jabeen, Ahad Mehmood, Zeeshan Abdullah, Mubarik Ali (Pakistan Journal of Medical & Health Sciences, 2022)
Neonatal jaundice (NNJ) is a significant pathological condition that causes morbidity and mortality in 80% of preterm infants and 50-60% of full-term newborns worldwide. NNJ can result in a variety of serious complications, including irreversible brain damage and, in severe cases, death. It is very critical for mothers to detect neonatal jaundice in the early stages of babies, so proper treatment, such as therapy, can begin. Mother knowledge, attitude, and practices are extremely important in the lives of newborn babies all over the world. This study was carried out in District Headquarters Hospital, KPK, Pakistan, to determine mothers’ knowledge, attitude, and practices regarding neonatal jaundice. A significant relationship between postnatal mothers’ knowledge and attitude toward neonatal jaundice was recorded in the current study. Almost 55% of mothers have a neutral attitude toward neonatal jaundice while 30% and 15% have a positive and negative attitude, respectively. The majority of mothers (30.75%) were between the ages of 21 and 25, while 25.75 and 24.50% were between the ages of 26-30 and 31-35, respectively. 64.250% of mothers were stay-at-home mothers, while 35.75% worked for the government. Illiterate (26.75%), primary (25.00%), middle (25.75%), higher (14.75%), and graduation (6.25%) level mothers participated, according to the data. Babies born to middle-class mothers had the highest rate of jaundice, followed by illiterate, primary, secondary, and graduate mothers. It was found that 55.50% of mothers had female babies and 44.50% of mothers had male babies. The majority of mothers (80.25%) were aware that jaundice changed skin colour, whereas 19.75% of mothers had a negative attitude toward skin colour. According to the majority of mothers, jaundice is a dangerous disease, while only 11.75% of mothers respond negatively. The participants in this study have a positive attitude toward Neonatal jaundice, their management measures and practices are ineffective and filled with misconceptions. More research on KAP in females is required. Keywords: Knowledge; Attitude; Practices; Neonate; Pakistan